“Sob a Aparência da Ordem”: um olhar sobre o policiamento solidário em João Pessoa-PB - Gomes de França, Fábio (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
The objective of this article is to present the results achieved through the analysis of the community policing project in the city of João Pessoa, Paraíba, which was named "Solidarity Police." To this end, we present a conclusive summary of what was obtained through the monitoring and observation of the daily routine of the solidarity policing posts and police actions. This allowed us to analyze a type of interaction present in the relationship between police officers and residents, which we have termed "strategic sociability." In this sense, what is at stake are biopolitical normalization processes that ratify state control over the communities involved in the project, as well as the strengthening of power relations that have a positive dimension because they are revealed through the discourse of a more democratic and citizen-oriented policing.
Keywords: Biopolitics; military police; solidarity policing